A Short Article on a Lively Subject: Geltruda Rossi, Sarah Siddons, and Shakespeare's Lady Macbeth à la Fuseli. Issue 1 (19th April 2017) - Burden, Michael
Abstract : In the 1784–85 London season, there was a conjunction between Shakespeare's Macbeth and three of the most thrilling artists of the eighteenth century: the dancer Geltruda Rossi, the actress Sarah Siddons, and the artist Henry Fuseli. They were thrown into figurative proximity when a commentator on Rossi's performance wrote in the Morning Herald and Daily Advertiser : "Madame Rossi, in Lady Macbeth, impresses one more with the recollection of Fusili 's [sic] painting, than of Mrs Siddons 's representation—indeed comparison would be doing an injustice to our critical and admired English performer." While we know much about the art of Siddons and Fuseli, we know little about Rossi's performances, which makes the Morning Herald 's parallel worth exploring as an example of eighteenth-century London ballet d'action .